Injectable, pH-responsive hybrid hydrogels for the treatment of periodontitis: The role of hybrid hydrogels on periodontitis - Zhu, Rui; Du, Wenhua; Mi, Xiaohui (Cellular and Molecular Biology, 2023)
Anti-inflammatory hydrogels have demonstrated great potential in the treatment of periodontitis. However, intelligent removal of reactive oxygen species (ROS) remains significantly challenging. In this study, a novel pH-responsive anti-inflammatory hydrogel was designed to treat periodontitis. We synthesized methacrylated alginate modified with a unique pH-sensitive phenylboronic acid through a one-step synthesis and then incorporated polydopamine particles loaded with minocycline to obtain a novel hydrogel under ultraviolet irradiation. Infrared and ultraviolet tests confirmed the successful preparation of the hydrogel. In environments with low pH, drug release rates significantly increased. In addition, in vitro cell experiments demonstrated excellent biocompatibility of the hydrogels. Furthermore, ROS detection revealed that the hydrogel effectively reduced cellular ROS levels and displayed excellent anti-inflammatory properties. These results strongly suggest that this novel pH-responsive anti-inflammatory hydrogel platform has tremendous potential for the treatment of periodontitis.